Portable anti-theft device - Johari Halim Shah, Nadira; Shafie, Aiman Fikrie; Azim, Akif Rusyaidi; Rosmin, Muhamad Nazim (Penerbit UTHM, 2020)
In this rapid-evolving era, theft and robbery cases related to electronic equipment and vehicles among Malaysians society are more serious and critical. Among the most common cases are related to laptop, car, motorcycle theft and more. Most stolen items cannot be neither traced nor found in the absence of appropriate security systems. A study released by Number in 2016 stated that the crime rate index in Malaysia is highest at 65.56 level. This is the highest crime index in Southeast Asia and the 15th in the world [1]. Clearly, this study has shown the seriousness of theft and robbery in Malaysia. Hence, in order to minimize the crime rate on this matter, a system of rifts is designed and named as "Portable Anti-Theft Device ".